Analisis Perkembangan dan Inovasi Senyawa Kompleks sebagai Agen Terapeutik dan Diagnostik dalam Kedokteran - Meli Sartika Silaban; Iis Siti Jahro (Yayasan Literasi Sains Indonesia, 2025)
Research advances in coordination chemistry have opened up significant opportunities for the development of complex compounds as therapeutic and diagnostic agents in medicine. This literature review aims to examine several important innovations that are beneficial in chemical and medical knowledge literacy, especially the literacy of cancer therapy applications using platinum, gold, ruthenium, gadolinium, technetium, and bismuth derivatives that have developed into first-line treatments for internal organ cancers such as ovarian, testicular, gastric, and lung cancer. The method used is descriptive qualitative research utilizing international journals and textbooks to support the literature review. The results of the study show the study of the use of metal-based compounds such as platinum, ruthenium, gold, bismuth, technetium, and gadolinium with broad potential, both as chemotherapeutic agents, anti-inflammatory, radiotherapy, and medical imaging contrast agents. This review discusses various procedures for the synthesis of these complex compounds and challenges such as drug resistance, toxicity, and limited bioavailability that remain major obstacles in their application. Therefore, it is necessary to develop the synthesis of complex compounds using innovative ligands that can increase selectivity, reduce toxicity, and improve bioavailability. Based on the results of the literature review, it was concluded that the integration of nanotechnology and coordination chemistry is recommended to improve therapeutic and diagnostic effects in medicine.